Enhanced Immunogenicity of Inactivated Dengue Vaccines by Novel Polysaccharide-Based Adjuvants in Mice - Shuenn-Jue Wu; Dan Ewing; Appavu K. Sundaram; Hua-Wei Chen; Zhaodong Liang; Ying Cheng; Vihasi Jani; Peifang Sun; Gregory D. Gromowski; Rafael A. De La Barrera; Megan A. Schilling; Nikolai Petrovsky; et al. (Microorganisms, 2022)
Dengue fever, caused by any of four dengue viruses (DENV1-4), is a major global burden. Currently, there is no effective vaccine that prevents infection in dengue naïve populations. We tested the ability of two novel adjuvants (Advax-PEI and Advax-2), using aluminum hydroxide (alum) as control, to enhance the immunogenicity of formalin- or psoralen-inactivated (PIV or PsIV) DENV2 vaccines in mice. Mice were vaccinated on days 0 and 30, and serum samples were collected on days 30, 60, 90, and 101. Neutralizing antibodies were determined by microneutralization (MN) assays, and the geometric mean 50% MN (MN50) titers were calculated. For the PIV groups, after one dose MN50 titers were higher in the novel adjuvant groups compared to the alum control, while MN50 titers were comparable between the adjuvant groups after the second dose. For the PsIV groups, both novel adjuvants induced higher MN50 titers than the alum control after the second dose. Spleen cells were collected on days 45 and 101 for enzyme-linked immunospot (ELISPOT) for IFNγ and IL4. Both PIV and PsIV groups elicited different degrees of IFNγ and IL4 responses. Overall, Advax-2 gave the best responses just ahead of Advax-PEI. Given Advax-2’s extensive human experience in other vaccine applications, it will be pursued for further development.